2018
DOI: 10.1017/jfm.2017.883
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous inertia–gravity wave emission in the differentially heated rotating annulus experiment

Abstract: The source mechanism of inertia–gravity waves (IGWs) observed in numerical simulations of the differentially heated rotating annulus experiment is investigated. The focus is on the wave generation from the balanced part of the flow, a process presumably contributing significantly to the atmospheric IGW field. Direct numerical simulations are performed for an atmosphere-like configuration of the annulus and possible regions of IGW activity are characterised by a Hilbert-transform algorithm. In addition, the flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
(114 reference statements)
2
9
0
5
Order By: Relevance
“…Although spontaneous imbalance has been documented from a number of numerical simulations also for the annulus configuration (Borchert et al (2014) and Hien et al (2018)) for which Reynolds number like in the experiment was rather small (Re 100) it has never been experimentally observed for the continuously stratified annulus for which in general the Rossby numbers are rather small and the flow is in a nearly balanced state. In our experiments the top layer shows wave packets in the horizontal divergence field travelling mainly with the frontal mean flow and hence much faster than the drift speed of the baroclinic waves.…”
Section: Discussionmentioning
confidence: 85%
“…Although spontaneous imbalance has been documented from a number of numerical simulations also for the annulus configuration (Borchert et al (2014) and Hien et al (2018)) for which Reynolds number like in the experiment was rather small (Re 100) it has never been experimentally observed for the continuously stratified annulus for which in general the Rossby numbers are rather small and the flow is in a nearly balanced state. In our experiments the top layer shows wave packets in the horizontal divergence field travelling mainly with the frontal mean flow and hence much faster than the drift speed of the baroclinic waves.…”
Section: Discussionmentioning
confidence: 85%
“…This variable is introduced to exhibit the occurrence of small-scale features simultaneously with the large-scale baroclinic waves. In the first plot, the small-scale structures, developing towards the bottom wall, have been identified as inertia gravity waves (IGWs) by different authors [37][38][39] in similar water-filled cavities. The present observed features recall such IGWs reported by these authors.…”
Section: Uniformly Rotating Flow With a Radial Temperature Gradient: mentioning
confidence: 99%
“…Since the pioneering works of Hide [12] , the differentially heated, rotating cylindrical annulus has been an archetypal means of studying the properties of fully-developed baroclinic instability in the laboratory. Recent works mainly based on direct numerical simulations reported the occurrence of IGWs in water-filled baroclinic cavity along the inner cold cylinder [37][38][39] . Moreover, Von Larcher et al [39] observed the presence of additional small-scale ripples resulting from hydrodynamical instability along the hot wall.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most fundamental physical modes in meteorology, gravity waves (GWs) are ubiquitous buoyancy oscillations in the atmosphere. The sources of excited gravity waves include, among others, topographic forcing (Smith 1980;Menchaca and Durran 2017), convection (Alexander et al 1995;Lane et al 2001), the jets Plougonven and Zhang 2014;Hien et al 2018), frontal systems (Snyder et al 1993; Griffiths and Reeder 1996), and shear instability (Bühler et al 1999;Bühler and McIntyre 1999). GW dynamics is also influenced by rotation, especially when the respective waves have relatively long horizontal wavelengths and short vertical wavelengths.…”
Section: Introductionmentioning
confidence: 99%